The Impact of Polygamous Parents on Children's Stress Level Development - Marzuqi, Muhammad Syafiq; Dinniar, Cindy Gefa Maulid (IJOSMAS, 2023)
Polygamy means multiple marriages. The etymological definition can be explained and understood that polygamy is a marriage in which one party (husband) marries more than one wife at the same time. This means that the wives are still dependent on the husband and are not divorced and are still valid as his wives. Many adults do not realize the mental importance of a child living as a